Mengurai Konflik dengan Mertua: Peran Hardiness Terhadap Stres Lingkungan pada Menantu Perempuan - Santi Nurhusaini; Rahmad Purnama; Khoiriyah Ulfah (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: Couples who live with parents (in-laws) have various dynamics in family life such as interpersonal conflict between daughters-in-law and in-laws. Interpersonal conflict can have a significant impact on the level of environmental stress experienced in the household environment, especially in daughters-in-law. So that the daughter-in-law needs considerable psychological resilience in dealing with the perceived environmental stress. Objective: This study aims to determine the relationship between interpersonal conflict of daughters-in-law on in-laws and hardiness on environmental stress. Method:This study used a quantitative correlational method with variance-based analysis techniques (Partial Least Square) and processed using Structural Equation Modeling (SEM). In this study there was a research sample of 326 daughters-in-law who lived with in-laws who were selected using purposive sampling techniques with research participant criteria such as age, education, length of marriage, and length of stay with in-laws. The instruments in the study consisted of environmental stress, interpersonal conflict, and hardiness scales. Result: The results showed that hardiness has a significant positive effect on environmental stress and interpersonal conflict also has a significant effect on environmental stress. Conclusion: The results of this study indicate that people with higher levels of hardiness tend to be better at dealing with environmental stress as a challenge. Conversely, high interpersonal conflict can increase environmental stress, so high resilience ability is needed to cope with the pressure that arises from interpersonal conflict. Keywords: Interpersonal Conflict, Hardiness, Environmental Stress, Daughter-in-law, In-laws